Who the frame a comparative content analysis of the framing of the Philippine Daily Inquirer and the Philippine Star of the 2016 P.E.T. case : Marcos V. Robredo - Umengan, Angelo Miguel L. 1993-
This study aimed to determine the extent of which the framing of the 2016 vie president election vote recount, the framing of vice president Leni Robredo, and the framing of Bong bong Marcos differ in the country's two leading broadsheets. It was a quantitative and qualitative research that observed the frames that news organizations use when reporting on electoral protests and post-election phenomenon. The study also sought to determine the causes of any perceived differences in the framing of this issue between the two broadsheets. The study employed a content analysis of hard news articles pertaining to the PET vote protest case and the preliminary stages leading up to the vote recounting. The study also used in-depth interviews as a research method. The research found that The Philippine Star and the Philippine Daily Inquirer have significant differences when it comes to the frames they prioritize when reporting on electoral protests. THough the broadsheets did not give equal coverage to the PET case, which might be a manifestation of bias and should be the subject of further study. The Conflict Frame was the most often used dominant frame when reporting on electoral protests, followed by the Attribution of Responsibility Frame.